Stres dalam kalangan kanak-kanak prasekolah orang asli kaum Senoi: kajian kes - Nor Aimi, Harun (2020)
Children of indigenous peoples are facing the effects of stress and this has not been widely and extensively discussed in scientific studies in Malaysia. Based on this, this qualitative case study was administered to identify the stress phenomenon that occurred among the Senoi-tribe students. The selection of the study sample involving a preschool child from the Senoi Tribe was based on the Stress Measurement Test instrument: Child and Adolescent Survey of Experiences (CASE). Data collection instruments used in this study were interviews, checklists, observations and reference documents. Data transcript analysis using Nvivo 0.8 software to help the data process store information. Findings showed that symptoms of stress such as underachievement, learning disabilities, PTSD, mood problems and onychophagia have been identified. The study also found that family, school and self-factors were identified as contributors to stress. The effects of stress behaviors that have been demonstrated by the study sample were delinquent behaviors ranging from aggressive behavior problems, vandalism and skipping school. Action re-experiencing, social isolation and selective silence were also the behavioral effects of stimulation of stress on Senoi children. Studies have also found that coping strategies which have been developed when facing stress stimulation were onychophagia, social isolation, aggressive behavior, lying and attachment. This study has implications for preschool teachers, parents and other stakeholders collectively and proactively to provide various forms of initiatives, support and programs for the development of Senoi children in an effort to protect them from the threat of stress in the future.